2017
DOI: 10.1371/journal.pone.0178851
|View full text |Cite
|
Sign up to set email alerts
|

Application of acoustic agglomeration to enhance air filtration efficiency in air-conditioning and mechanical ventilation (ACMV) systems

Abstract: The recent episodes of haze in Southeast Asia have caused some of the worst regional atmospheric pollution ever recorded in history. In order to control the levels of airborne fine particulate matters (PM) indoors, filtration systems providing high PM capturing efficiency are often sought, which inadvertently also results in high airflow resistance (or pressure drop) that increases the energy consumption for air distribution. A pre-conditioning mechanism promoting the formation of particle clusters to enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 139 publications
1
23
0
8
Order By: Relevance
“…Acoustic agglomeration, as a preconditioning technique, is a process in which small particles in a suspension collide with one another to form large agglomerates under the action of a sound field. As a result, particle size distribution can shift significantly to a range of larger particulates within a short period of time, and the efficiency of conventional particle removal technologies is greatly improved Sarabia et al 1986;Malherbe et al 1988;Caperan et al 1995;Gallego-Juarez et al 1999;Yuen et al 2014;Ma et al 2017;Ng et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic agglomeration, as a preconditioning technique, is a process in which small particles in a suspension collide with one another to form large agglomerates under the action of a sound field. As a result, particle size distribution can shift significantly to a range of larger particulates within a short period of time, and the efficiency of conventional particle removal technologies is greatly improved Sarabia et al 1986;Malherbe et al 1988;Caperan et al 1995;Gallego-Juarez et al 1999;Yuen et al 2014;Ma et al 2017;Ng et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, constructive ways to increase the efficiency of collecting fine fractions of the most commonly used collectors are practically ex hausted and most of the work is aimed at finding a solu tion to this problem by influencing the fractional compo sition of dust. In works [9,10], it is suggested that the acoustic coagulation of fine dust be made before the col lector, and in the work [11], the high frequency sound waves bands, that provide the best results, are defined. The main drawback of the method is the need to use ad ditional equipment -an acoustic wave generator.…”
mentioning
confidence: 99%
“…Specifically, increase of indoor bioaerosol concentrations due to bioaerosol emission from the ACMV system has not been observed and bioaerosol emission of the ACMV system is still not quantified and species-identified, which makes it debatable that whether the ACMV system is helping to control indoor bioaerosol level or is worsening indoor air by emitting bioaerosols to indoor space. In addition to being potential bioaerosol emission source for the indoor space, the operation of ACMV systems accounts for nearly half of the total building electricity consumption in buildings under temperate climate and this can reach 70% for buildings in the tropics, where ACMV systems usually operate for longer time in a day compared to their operation in temperate indoor environment (Ng et al, 2017). Therefore, it is necessary to develop new approaches to avoid the significant energy consumption of operation of the ACMV system while control indoor pollutants level effectively.…”
Section: List Of Tablesmentioning
confidence: 99%
“…The operation of ACMV systems accounts for nearly half of the total building electricity consumption in buildings under temperate climate (Pérez-Lombard et al, 2008) and this can reach 70% for buildings in the tropics, where ACMV systems usually operate for longer time in a day compared to their operation in template indoor environment (Ng et al, 2017). In buildings, energy consumption of operation of the ACMV system is predominant compared with other energy use such as lighting and appliance.…”
Section: Conditioning and Mechanical Ventilation Systemmentioning
confidence: 99%
See 1 more Smart Citation